Unveiling Students’ Experience with Project-Based Learning in Higher Education - Silvani, Dea; Santiana, Santiana; Syakira, Sitti (Siliwangi University, 2025)
Project-Based Learning (PjBL) has garnered considerable attention as an innovative pedagogical technique that fosters active participation, analytical reasoning, and tangible utilization of acquired knowledge. This study explores the experience of undergraduate students focusing on the benefits, challenges and coping strategies during the implementation of project-based learning (PjBL) in an ESP course. Involving 45 English Education Department students as the participants, this mixed methods study utilized questionnaire and semi-structured interviews to obtain the data regarding their experience while joining PjBL. The quantitative data from the questionnaire were analysed by using descriptive statistics, while the qualitative data from the interview were analysed through the steps of data condensation, data display, and conclusion drawing. The results of this research indicate that students recognized the roles of PjBL in enhancing their learning motivation, engagement, understanding, language proficiency, problem solving, critical thinking, creativity, and collaboration skills. However, this study also reported significant challenges regarding time constraints, resourcing difficulties, and collaboration issues. To address these challenges, students employed various strategies such as managing tasks independently, utilizing accessible resources, and maintaining effective communication. This study concludes that when carefully implemented, PjBL can be an effective instructional method in ESP contexts that offers meaningful opportunities for both linguistic and personal development. Keywords: Project based Learning, learning experience, higher education, ESP